Computed Tomographic Evaluation of Renal Mass with Histopathological Correlation (Bangladesh Medical Journal, 2023)
Renal cell carcinoma (RCC) is the seventh most common cancer and the most common primary renal malignant neoplasm in adults. Computed Tomography (CT) is of a great value in differentiating malignant from benign masses of RCC. This cross-sectional study was conducted among 61 clinically suspected cases of renal mass at Sir Salimullah Medical College and Mitford Hospital (SSMC and Mitford Hospital) in the Department of Radiology and Imaging in collaboration with the Department of Urology and Pathology, from July ’2011 to June’ 2013. However, in 05 cases, histopathological reports were not available and 07 patients refused surgery after enrolling. Finally, histopathology reports were collected from 49 patients and they were considered as study subjects. Aim of the study was to evaluate the accuracy of CT scan findings in compere with the histopathological report for the diagnosis of renal mass and to differentiate its benign and malignant forms. The age range of the patients was 2 to 73 years, where more than two-third (69.38%) were male and rest of them were female. Maximum number of malignant cases observed in the age range of 50-59 years. In comparison, inflammatory and benign conditions dominate in early age group, mostly before 40 years. Among 49 cases, 41 (83.68%) cases were diagnosed as malignant renal mass by CT scan, 01 (2.04) case was missed, which was confirmed by histopathology. Rest 07 (14.28%) patients were diagnosed as benign both in CT scan and histopathology. The sensitivity of CT for malignant renal mass was found 97.62% and specificity was 100%. The positive and negative predictive values of CT were 87.5% and 97.59% respectively. Computed tomography is a valid diagnostic modality for differentiating benign and malignant renal mass.Bangladesh Med J. 2021 Sept; 51(1): 41-46